Exploring the nexus between sustainable energy tokens, electric vehicles, and the hydrogen economy - Mbarek, Marouene (Research in international business and finance, 2025)
The aim of this research is to explore the transmission of tail risk between energy tokens and sustainable equity sectors, specifically focusing on the electric vehicle industry (EVI) and the hydrogen economy (HEI). To achieve this objective, we combine the Conditional Autoregressive Value at Risk (CAViaR) model with the Time-Varying Granger-Causality (TVGC) method and the Wavelet Coherency approach, over the period from April 8, 2020, to February 16, 2024. The TVGC results reveal unidirectional causal relationships from energy tokens to these equity sectors. However, bidirectional causality exists between SNC and HEI. These causalities predominantly occur during significant events such as the Covid-19 pandemic, the cryptocurrency bubble, the Russian-Ukrainian conflict, and the collapses of FTX and SVB. These findings are consistent with those identified by the Wavelet coherency method, which shows variability in the frequency of causality between energy tokens and equity sectors. Additionally, the assessment of portfolio implications based on CAViaR’s 5 % VaR for pairs of markets demonstrates the ability of energy tokens to mitigate tail risk transmission when incorporated into portfolios of electric vehicle and hydrogen economy equities. These insights are valuable for crypto managers and investors in adjusting and optimizing their hedging strategies. [Display omitted] •This study investigates tail risk transmission between energy tokens and sustainable equity sectors, including electric vehicles (EVI) and the hydrogen economy (HEI).•Using CAViaR, time-varying Granger causality, and wavelet coherence, the analysis reveals short-lived and event-driven causal linkages during financial stress.•Energy tokens offer diversification benefits in stable markets but limited hedging effectiveness.•The study provides practical guidance for investors and regulators on portfolio risk management in sustainable finance.